Evaluation of the antimicrobial effect of super-oxidized water (Sterilox®) and sodium hypochlorite against Enterococcus faecalis in a bovine root canal model (Journal of Applied Oral Science, 2010)
ABSTRACT Ideally root canal irrigants should have, amongst other properties, antimicrobial action associated with a lack of toxicity against periapical tissues. Sodium hypochlorite (NaOCl) is a widely used root canal irrigant, however it has been shown to have a cytotoxic effect on vital tissue and therefore it is prudent to investigate alternative irrigants. Sterilox's Aquatine Alpha Electrolyte® belongs to the group of the super-oxidized waters; it consists of a mixture of oxidizing substances, and has been suggested to be used as root canal irrigant. Super-oxidized waters have been shown to provide efficient cleaning of root canal walls, and have been proposed to be used for the disinfection of medical equipment. OBJECTIVE: To compare the antimicrobial action against Enterococcus faecalis of NaOCl, Optident Sterilox Electrolyte Solution® and Sterilox's Aquatine Alpha Electrolyte® when used as irrigating solutions in a bovine root canal model. METHODOLOGY: Root sections were prepared and inoculated with E. faecalis JH2-2. After 10 days of incubation the root canals were irrigated using one of three solutions (NaOCl, Optident Sterilox Electrolyte Solution®and Sterilox's Aquatine Alpha Electrolyte®) and subsequently sampled by grinding dentin using drills. The debris was placed in BHI broth and dilutions were plated onto fresh agar plates to quantify growth. RESULTS: Sodium hypochlorite was the only irrigant to eliminate all bacteria. When the dilutions were made, although NaOCl was still statistically superior, Sterilox's Aquatine Alpha Electrolyte® solution was superior to Optident Sterilox Electrolyte Solution®. CONCLUSIONS: Under the conditions of this study Sterilox's Aquatine Alpha Electrolyte® appeared to have significantly more antimicrobial action compared to the Optident Sterilox Electrolyte Solution® alone, however NaOCl was the only solution able to consistently eradicate E. faecalis in the model.